Vacuum-assisted venous drainage in extrathoracic cardiopulmonary bypass management during minimally invasive cardiac surgery. - Colangelo N; Torracca L; Lapenna E; Moriggia S; Crescenzi G; Alfieri O (Perfusion, 2006)
The diffusion of minimally invasive cardiac surgery (MICS) during open-heart surgery has increased the use of assisted venous drainage support for cardiopulmonary bypass (CPB). Peripheral cannulation with small cannulae and vacuum-assisted venous drainage (VAVD) during MICS has been adopted in our institution since 1998. After the Heartport technique (HP) experience, the trans-thoracic clamp technique is now currently used. The aim of this study is to report our experience with extrathoracic CPB with VAVD application (on CPB) during open-heart MICS. From October 1999 to June 2006, 193 patients underwent MICS. Thirty-seven (19.2%) patients were treated with the HP--13 (35%) with robotic technology and 156 (80.8%) with trans-thoracic aortic clamping (TTAC). Mean age was 39 years (range: 12-77), and 114 patients (59.1%) were female. A total of 128 patients (66.3%) underwent mitral valve surgery, 57 (29.6%) atrial septal defect closure, five (2.6%) cardiac mass removal, and three (1.5%) tricuspid valve repair. Four patients (2.0%) had a previous cardiac procedure. Peripheral CPB was established with a standard coated circuit. A 14 Fr arterial cannula was inserted into the right jugular vein and positioned at the atrial/superior vena cava junction. A 21 or 28 percutaneous femoral cannula, depending on body surface area, was inserted in the femoral vein and an arterial cannula in the right femoral artery. Gravitational drainage was combined with VAVD. To improve the safety and effectiveness of this technique, we monitored the pressure on each venous cannula and in the reservoir. The mean CPB time was 74.8 +/- 30 min (TTAC) and 119 +/- 48 min (HP); mean aortic clamping time was 51 +/- 19 min (TTAC) and 73 +/- 29 min (HP). We did not record any neurological complication. Two patients (1.0%), one from each group, were converted to sternotomy. Three patients (1.5%) underwent re-exploration for bleeding. In-hospital mortality was 0.5% (N = 1) (HP). Mechanical ventilation time and intensive care unit stay were comparable to those recorded with conventional sternotomy. In conclusion, we found that extrathoracic CPB and VAVD during trans-thoracic clamping is a safe, simple, and effective technique for MICS. However, there is a potential risk of haemolysis and air embolism, which can be prevented with vacuum monitoring, and with the addition of gravitational drainage to reduce vacuum pressure.